Hedonism as Seen in Oscar Wilde’s "The Picture of Dorian Gray" - Anastasia Intan Kurnia Saputri (Lexicon, 2015)
This article discusses hedonism in Oscar Wilde’s The Picture of Dorian Gray through the main character’s actions and lifestyle. The Picture of Dorian Gray (1890) was published in the era where aestheticism movement was flourishing. Aestheticism is an arts movement that promoted art for the sake of its beauty alone. This movement is believed to be existed as a protest against the machine-made products in the Industrial Revolution which were regarded to be ugly. Therefore, the whole story of The Picture of Dorian Gray concerns about beauty. By analyzing the main character, this article aims to find out the role of the supporting characters, the similarity of Dorian’s lifestyle with the real Victorian gentlemen, and the role of beauty and art in Dorian Gray’s changing behavior. This study is conducted through library and internet research. It concludes that the main character Dorian Gray has undergone a process that changes his behavior which is involving the role of the supporting characters, the similarity of gentlemen’s lifestyle in the story with the real Victorian society, and the role of beauty and art which overall have changed Dorian’s behavior and lifestyle to the point where it can be regarded as hedonic.